Interações positivas entre actinobactérias e rizóbios oriundos de áreas antropizadas do semiárido - Sousa, Juliani Barbosa de (2020)
Soil is a heterogeneous environment composed of a huge diversity of microorganisms that playa key role in ecosystems. Actinobacteria and nitrogen-fixing bacteria are important membersof the edaphic community, due to the relevance of these microbial groups, so the understandingof the interactions between them has been studied due to their importance. In the semi-aridnortheast of which they are part, where resources are scarce and there is concern of the academiccommunity regarding the loss of biodiversity, it is essential to know the biological diversity andits behavior in this context. This research is based on the study of the positive interactionsbetween actinobacteria and rhizobium from the semi-arid region, as a way to contribute toecological studies and conservation of the Caatinga biome. This thesis includes 3 chapterswhose objectives were to evaluate the changes in publications on positive and negativeinteractions between actinobacteria and rhizobium, identifying gaps in knowledge and prioritiesfor future studies; to evaluate the enzymatic profile of actinobacteria and rhizobium from thesemi-arid northeast and verify the occurrence of in vitro facilitation; and to assess the effect ofco-inoculation, in an in vivo experiment, of actinobacteria and rhizobium strains on thephysiological and biometric characteristics of cowpea (Vigna unguiculata).